Dangerous Driving Among Heavy Vehicle Drivers Along Jalan Batu Pahat-Kluang (FT050) - anak Edward, Terence Telajan; David Daniel, Basil (Recent Trends in Civil Engineering and Built Environment, 2021)
Dangerous driving behavior among heavy vehicles drivers at Jalan Batu Pahat-Kluang such as speeding which is the main reason that have made the highway as one of the most lethal highway in Malaysia. This research will help to identify the type and rate of dangerous driving among commercial vehicle and bus drivers as well as to determine the speed limit compliance among heavy vehicles during morning and afternoon at this highway. Video recording method are used to collect data while the Poisson Probability method are applied to the data to get the likelihood of committing dangerous driving and Hypothesis Testing are used to know the compliance of the speed limit at the highway. The result of this study found out that speeding and driving in the fast lane are the most common type of dangerous driving which that have an average of 20.67 speeding committed per hour at Km-15 while driving in the fast lane are mostly committed at Km-24.5 with an average of 14.58 per hour. Other than that, heavy vehicles drivers at certain area of the road does not comply with the speed limit. In conclusion, there are still some probability of dangerous driving such as speeding and not complying with the speed limit to be committed, therefore the installation of speed trap camera would help to decrease the probability and reduces the chance of accident to happen.